Breaking the deadlock : the 2000 election, the constitution, and the courts - Posner, Richard A. (Princeton University Press, 2001)
Judge Posner surveys the history and theory of American electoral law and practice, analyzes which Presidential candidate "really" won the popular vote in Florida, surveys the litigation that ensued, evaluates the courts, the lawyers, and the commentators, and ends with a blueprint for reforming our Presidential electoral practices.